Biodiversity offsets in South Africa – challenges and potential solutions. Issue 3 (3rd July 2017) - Brownlie, Susie; von Hase, Amrei; Botha, Mark; Manuel, Jeffrey; Balmforth, Zoe; Jenner, Nicky
Abstract: South Africa has a decade of experience designing and implementing biodiversity offsets. In the absence of explicit national policy on biodiversity offsets, the country has relied on existing legal provisions in environmental law as the basis for offset requirements, supported by provincial guidelines. South Africa's periodic national biodiversity surveys provide scientifically rigorous quantification and mapping for individual ecosystems and finer scale surveys identify biodiversity priority areas, primed as 'offset receiving areas'. Yet despite enabling factors the use of offsets has frequently been inadequate to deliver intended biodiversity outcomes. Challenges include: (a) the absence of national policy to drive and shape offset implementation; (b) insufficient capacity to evaluate, design and implement offsets; (c) inconsistent decision-making; (d) problems establishing sustainable financing mechanisms; and (e) inadequate enforcement and monitoring, linked to poor drafting of licencing conditions and/or insufficient capacity to monitor implementation. South Africa's experience provides valuable insights into the challenges and potential solutions for making offsets work for biodiversity conservation and offers important lessons for the development and implementation of biodiversity offsetting in other developing countries.